Faith-based organisations and exclusion in European cities - Beaumont, Justin 1973-; Cloke, Paul 1953- (Policy, 2012)
This timely book explores the role played by faith-based organisations (FBOs), which are growing in importance in the provision of social services in the European context
Title from publisher's bibliographic system (viewed on 07 Sep 2022)
Keywords: Religious institutions / Social aspects / Europe; Marginality, Social / Europe; Marginality, Social / Religious aspects; Sociology, Urban / Europe; Glaube; Religiöse Einrichtung; Religion; Religiöse Organisation; Ausgrenzung; Europa; Aufsatzsammlung